Motivasi Atlet Putri Floorball Jawa Timur Dalam Menghadapi Kejuaraan Nasional 2024 - Utami, Tiffanny Tessantya; Bakti, Ananda Pewira; Pudjijuniarto, Pudjijuniarto; Khuddus, Lutfhi Abdil (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This research examines female floorball athletes in East Java, where there are annual changes in athletes, with each individual experiencing fluctuations in motivation levels in achieving success. The aim of this research is to determine the level of motivation of East Java female floorball athletes in facing the 2024 national championship and to evaluate the overall level of motivation, as well as the sub-variables of intrinsic motivation and extrinsic motivation. This research employs a quantitative descriptive approach. The research subjects comprised 25 East Java female floorball athletes who will participate in the national championship. Data collection was conducted using a questionnaire consisting of 38 statements, analyzed using descriptive percentages and categorized according to an interval table. The results indicated that the overall level of motivation was good (44%), the level of intrinsic motivation was good (40%), and the level of extrinsic motivation was good (44%). These findings suggest that intrinsic motivation plays a more significant role for athletes. In conclusion, the motivation of East Java female floorball athletes in facing the 2024 national championship is good.